The impact of solar ultraviolet radiation on human health in sub-Saharan Africa - Caradee Wright; Mary Norval; Beverley Summers; Lester Davids; Gerrie Coetzee; Matthew Oriowo (South African Journal of Science, 2012)
Photoprotection messages and ‘SunSmart’ programmes exist mainly to prevent skin cancers and, more recently, to encourage adequate personal sun exposure to elicit a vitamin D response for healthy bone and immune systems. Several developed countries maintain intensive research networks and monitor solar UV radiation to support awareness campaigns and intervention development. The situation is different in sub-Saharan Africa. Adequate empirical evidence of the impact of solar UV radiation on human health, even for melanomas and cataracts, is lacking, and is overshadowed by other factors such as communicable diseases, especially HIV, AIDS and tuberculosis. In addition, the established photoprotection messages used in developed countries have been adopted and implemented in a limited number of sub-Saharan countries but with minimal understanding of local conditions and behaviours. In this review, we consider the current evidence for sun-related effects on human health in sub-Saharan Africa, summarise published research and identify key issues. Data on the prevalence of human diseases affected by solar UV radiation in all subpopulations are not generally available, financial support is insufficient and the infrastructure to address these and other related topics is inadequate. Despite these limitations, considerable progress may be made regarding the management of solar UV radiation related health outcomes in sub-Saharan Africa, provided researchers collaborate and resources are allocated appropriately.